LARP1 post-transcriptionally regulates mTOR and contributes to cancer progression - Blagden, S; Bushell, M; Willis, A; Mura, M; Hopkins, T; Michael, T; Abd-Latip, N; Curry, E; Weir, J; Aboagye, E; Sturge, J; Jameson, C; et al. (Nature Publishing Group: Open Access Hybrid Model Option B, 2015)
RNA-binding proteins (RBPs) bind to and post-transcriptionally regulate the stability of mRNAs. La-related protein 1 (LARP1) is a conserved RBP that interacts with poly-A-binding protein and is known to regulate 5′-terminal oligopyrimidine tract (TOP) mRNA translation. Here, we show that LARP1 is complexed to 3000 mRNAs enriched for cancer pathways. A prominent member of the LARP1 interactome is mTOR whose mRNA transcript is stabilized by LARP1. At a functional level, we show that LARP1 promotes cell migration, invasion, anchorage-independent growth and in vivo tumorigenesis. Furthermore, we show that LARP1 expression is elevated in epithelial cancers such as cervical and non-small cell lung cancers, where its expression correlates with disease progression and adverse prognosis, respectively. We therefore conclude that, through the post-transcriptional regulation of genes such as mTOR within cancer pathways, LARP1 contributes to cancer progression.